EFFECTS OF HEAVY METAL TOXICITY ON BIOTA OF FRESHWATER AQUATIC ECOSYSTEMS (International Journal of Food and Nutritional Sciences, 2023)
The contamination of aquatic habitats caused by human and natural activity has made studying them a major concern nowadays. Due to bioaccumulation and biomagnification, heavy metal contamination of freshwater ecosystems is a global issue brought on by urbanization and industrialization. This pollution poses a hazard to both aquatic and terrestrial ecosystems. Freshwater fishes' dietary patterns and tissue affinity for specific heavy metals are the reasons behind the bioaccumulation of some heavy metals. This review highlights the sources of non-essential heavy metal contamination such as arsenic (As), Cadmium (Cd), Lead (Pb), and Mercury (Hg). The bioaccumulation factor of heavy metals in the food chain is prone to biomagnification in the tissues, which then impacts the biota concerning freshwater aquatic ecosystems.